Mobile commerce : how it contrasts, challenges and enhances electronic commerce - Swilley, Esther. (Digital and social media marketing and advertising collection., 2016)
Do you know anyone who does not own a mobile device? Consumers use mobile devices not only for communicating but for shopping as well. Searching for product information, inquiring about services, comparing prices, and purchasing make up just some of the shopping functions done on mobile devices. How does digital change how firms do business? What are the differences between desktop computer shoppers and mobile device shoppers? Moreover, are firms prepared to do business in this changing environment? As tablet owners relax in the evenings, they are powering up those tablets, and using tablet time for shopping. Does this behavior differ from those sitting at their desktop computers and browse online? Understanding the differences between those shopping in electronic commerce and those purchasing in mobile commerce allows firms to gain a larger foothold in the digital commerce market. The purpose of this book is to answer questions concerning the benefits of mobile commerce and its commonalities and contrasts with electronic commerce. Electronic commerce is still viable and we examine its validity along with mobile commerce. Mobile commerce is not electronic commerce, and we discuss the differences, as well as how one can enhance the other. Consumers use both electronic commerce and mobile commerce, as well as offline shopping, on their path to purchase in total omnichannel environment--using all channels. We integrate the opportunities and challenges to bring an idea of the future of marketing with an emphasis on both mobile and electronic commerce, into digital commerce.